PLOT IN A COLLECTION OF SHORT STORIES “SAKINAH BERSAMAMU” WRITTEN BY ASMA NADIA WITH FEMINIMISM ANALYSIS - Noermanzah Noe Noermanzah (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2017)
PLOT DALAM KUMPULAN CERPEN SAKINAH BERSAMAMU KARYA ASMA NADIA DENGAN ANALISIS FEMINIMISMEAbstractThis study aims to obtain an understanding about the plot in a collection of short stories